Onychomycosis: role of non dermatophytes - Narain, Upma; Bajaj, Ashok Kumar (International Journal of Advances in Medicine, 2016)
Background: Onychomycosis, a fungal infection of nails, is ordinarily be caused by dermatophytes, non dermatophytes and yeast. Therefore the aim of this study was to determine the role and pattern of non dermatophyte moulds as causative agents of onychomycosis. Methods: The retrospective study was carried out from Jan, 2000 to March, 2014 at Allahabad. In more than a period of 14 years 3321 clinically suspected cases of onychomycosis are included in the study. KOH examination and culture have been carried out in all the patients. All the finger and toe nails were examined along with whole body skin for fungal infection. Results: Positive cultures were obtained in 2906 cases. Dermatophytes were isolated in 1307 (44.97%), non dermatophytes in 1209 (41.60%), yeast in 284 (9.77%), mixed infections in 106 (3.64%) cases, and the remaining 415 cultures were sterile. Among ND the predominant isolates obtained were Scopulariopsis bervicaulis (20.51%), Aspergillus terreus (14.06%), Aspergillus niger (7.44%), Aspergillus flavus (8.10%), Absidia (7.22%), Rhizopus (7.60%), Acremonium (11.99%), Fusarium (7.60%), Penicillium (8.22%), Mucor (5.78%), and Scytalidium dimidiatum (1.48%). Conclusions: It can be inferred from the study that NDMs play a significant role in the causation of onychomycosis. Hence it is necessary that fungus culture should be carried out in all cases of onychomycosis for proper therapeutic management.